2014
DOI: 10.5897/ajmr12.1021
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and antimicrobial bioactivity of the Algerian parsley essential oil (Petroselinum crispum)

Abstract: In this paper, we extracted, analyzed and studied the antimicrobial activity of Algerian parsley essential oil on several microbes that cause infectious diseases and its effects on kinetics of lactic acid production by Lactobacillus casei subsp. rhamnosus. The essential oil of parsley (Petroselinum crispum Hoffm) obtained by hydrodistillation was characterized by its physicochemical properties and by its chromatographic profiles. Myristicin and dillapiol were identified by gas chromatographyspectrometry mass (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The composition of the control sample in the present study was similar to that reported in Ouis et al [14] for an EO hydrodistilled from a specimen of P. crispum from ex-Yugoslavia (the current name of the country is not reported), in which myristicin (60.5%), 1,3,8-p-menthatriene (20.1%) and β-phellandrene (6.2%) were the most abundant compounds. Also in Petropoulos et al [15], the EO of P. crispum Subsp.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The composition of the control sample in the present study was similar to that reported in Ouis et al [14] for an EO hydrodistilled from a specimen of P. crispum from ex-Yugoslavia (the current name of the country is not reported), in which myristicin (60.5%), 1,3,8-p-menthatriene (20.1%) and β-phellandrene (6.2%) were the most abundant compounds. Also in Petropoulos et al [15], the EO of P. crispum Subsp.…”
Section: Discussionsupporting
confidence: 88%
“…Phenylpropanoids, specifically myristicin and apiole, were abundant compounds in many P. crispum EOs from different countries: Serbia [16], Brazil [17] and Egypt [18]; other published EOs compositions showed the same behavior, but their geographical origin was not reported [19,20]. Monoterpene hydrocarbons were more abundant in the EOs hydrodistilled from Middle Eastern samples: Turkish parsley EO was mainly composed by 1,3,8-p-menthatriene, β-phellandrene, and myrcene [14]; 1,3,8-p-menthatriene, terpinolene, and myrcene were the most represented VOCs in the EO of Saudi Arabia parsley [14]; the Iranian sample in Ouis et al [14] showed an intermediate behavior between the last two EOs. Kiralan et al [21] reported an EO composition mainly composed by αand β-pinene, followed by apiole and 2,3,4,5-tetramethoxy-1-allylbenzene: the sample was from Mosul, Iraq.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Linde et al, revealed that the major compounds in Brazilian parsley were apiol (50.3 %) and myristicin (14.0 %) [ 8 ]. Apiol and myristicin have consistently been among the major constituents of parsley essential oil worldwide [ 34 ]. Therefore, the quantities of apiole in our samples were similar to those described in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Parsley, Spanish scolyme and white horehound are among the most widely used plants in traditional Algerian and North African medicine (Belakhdar, 1998;Elyebdri et al, 2017) for their diuretic and antilithiasic properties (Lahsissene et al, 2010;Tahri et al, 2012;Zeggwagh et al, 2013;Ouis et al, 2014). According to Bentham (Agyare et al, 2017), Algeria is among the countries where parsley originated.…”
Section: Introductionmentioning
confidence: 99%